The Changing Functions of Villages and Hamlets in Wellington County, 1881-1971 - Dahms, F. (Urban History Review / Revue d'histoire urbaine, 1980)
Despite centralization of population and economic activity during the last hundred years, villages and hamlets in the Guelph area have not "died." New functions have replaced many that disappeared, while the increasing use of the car has led to a proliferation of service stations, and to more economic diversity in the largest places. Commuters have increased the populations of many small settlements with good access to employment in cities. If gasoline prices continue to rise, many small places may again experience slower growth and relative economic stagnation.